Development of Assessment Instruments for Critical Thinking Ability in Basic Work Lessons of Industrial Class Engineering SMKN 26 Jakarta - Jumhur, Aam Amaningsih; Mahir, Imam; Avianti, Ratu Amilia; Susilawati, Risa (Journal of Education Research and Evaluation, 2021)
This research hasi.purpose designing instruments. ability assessment .critical thinking, get the results of the instrument. assessment of thinking skills.critically valid.and reliable. The research method used is Research and Development, using methods.4D development, namely 1) observation and study of literature, 2) expert validation test, 3) testing for students, 4) ready-to-use product. The results of this study obtained. the result of that type.research instrument. which is developed feasible. used with analysis indicators, interpretation,. inference, evaluation, explanation,.induction, Decuction. The assessment instrument developed was PG (Multiple Choice). The difficulty test shows that of the 40 questions made have a difficulty level of 0.27 to 0.44, which is in the difficult and moderate criteria, on the test results 5 questions are stated as good, 17 questions are stated as sufficient, and 18 questions are said to be bad. The instrument for assessing critical thinking skills in basic mechanical engineering subjects was declared valid for 30 out of the 40 questions made and the reliability value was 0.82, then it was declared as realistic. Conclusion, the instrument for assessing critical thinking skills in the basic engineering work course is feasible.